Penggunaan Chlorella sp. sebagai Alternatif untuk Mengolah Limbah Cair Industri Pengolahan Susu - Yuli Pratiwi (Eksergi, 2022)
One of methods of treating waste in the most efective and chepest way is by biological method because it utilize mícrobes that are abundant in natural etwironment. Microbe actívities can be utilízed to produce a system that can accomplish recycling process, so they can control the quality of waste. This research is aimed to carry out test by utilizing microbes Chlorella sp. that is belonged to phytoplanktons that are used as innoculum for treating waste miIk industry. The research was conducted at the Environmental Technical Laborotory of ISTA Yogtøkortarta for 3 months, wíth activities starting from Chlorella sp. culturing, preliminary research for determining the concentration of optimal inocallum growth to the main research, the application of Chlorella sp. for milk waste treatment. From the result of research, it was evident that milkwaste milk Índustry exerted positive influence on the growth of Chlorella sp. that could reached optimal rate. The optimal growth rate, in turn, could be utilized to improve milkwaste quality, especially to reduce BOD, soluble CO, and to íncrease DO as well as to neutralize pH. Other efect of optimal Chlorellasp. growth was that protozoa populatíon growth that sustain and acceleratethe treatment of this milkwaste.